ANALISIS PENGARUH AUDIT TENURE, ROTASI KAP, UKURAN KAP, DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Sulthon, Muhajir; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2015)
This study purposed to explore the empirical evidence regarding the effect of audit tenure, the rotation of the audit, the size of the public accounting firm, and audit committee on aud it quality. This study uses three control variables which are firm size, firm risk, and growth of the company. The  population of this study is all manufactur companies listed in Indonesia Stock Exchange 2008-2013. The criterias of the sample are manufacturing companies listed in Indonesia Stock Exchange on January 1, 2008 until December 31, 2013, and the company has a complete data for all variables measurement. The total  sample consists   to  71  companies.  this study uses  multiple regression. The results showed that audit tenure, audit rotation, the size of public accounting firm, and   audit committee have a significant effect on audit quality. In this study audit tenure has a negative effect to the audit quality, it shows that longer audit tenure public aco ounting produces better audit quality